Field notes contributed by Francis L. Moore, spring 1984 - Moore, Francis L.et al (1984)
Field notes were contributed by Francis L. Moore, spring 1984, with five other observers. Among dozens of species listed, the following were documented: Red-throated Loon at Cedar Lake, Red-necked Grebe at Little Wall Lake, Ross' Goose at Willow Slough, Eurasian Wigeon at Sweet Marsh, Barrow's Goldeneye at Forneys Lake, Northern Goshawk at Big Marsh and west of Cedar Falls, Merlin near Sweet Marsh, Peregrine Falcon at Sweet Marsh and Riverton Wildlife Area, and Marbled Godwit north of Waterloo. A separate document by Moore called "Notes to field reports" explains details of some other sightings. The other observers were: Robert K. Myers, W. Ross Silcock, Dan Perkins, Raymond L. Cummins, and Russell Hays. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed